Role of Lean and Agile Supply Chain Models for Pellet Fuel Technologies - Szendrei, János; Kocsi, Balázs; Budai, István; Grasselli, Gábor; Szűcs, Edit (International Journal of Engineering and Management Sciences, 2017)
Business organisations constantly strive to improve their processes, both internal and external. Within the supply chain of a product, different strategies can be applied. This paper aims to answer the basic questions like what is the core of lean and agile SCM strategies, what are the differences of the two models, and how can they be combined. This paper examines further, which of these SCM models and what elements of them can be applied for wood pellet supply chains, also examining the possibility of their combination. The result of these examinations is, that even though fuel pellets can be considered as simple commodity and not a very innovative product, diversity in input characteristics, optimization of fuel pellet technology process variables and changes in output market qualities and quantities need sometimes agile, flexible answer from pellet fuel SCM. The basically lean character of pellet fuel technologies and SCM can further enhanced by implementing agile SCM model elements, as is the increased integration of suppliers into the supply chain.